Nature of the Construction Industry, Its Needs and Its Development: A Review of Four Decades of Research - Ofori, George (Penerbit Universiti Sains Malaysia, 2015)
The construction industry is not well understood. There is no common definition, and there are even arguments about whether it is an industry or a sector that comprises many industries. The contribution of the construction industry to economic growth and long-term national development is widely acknowledged, highlighting its importance, particularly to developing countries. For the benefit of these countries, it is important to investigate the nature, essential characteristics and particular requirements of the construction industry and to use them to develop programmes for its improvement. A research programme that started in 1974 and is still continuing is discussed. The subjects studied in the research programme have included the nature of the construction industry, its importance in development, its needs and its development. Elements of the process of construction industry development that have been studied include ways and means of improving the performance of construction firms, focusing on contractors and technology development. The findings from these early studies influenced the formulation of policies and legislation for establishing construction industry development agencies in a number of countries. Other aspects of the construction industry that are studied in the research programme include the parameters of performance in the industry, such as productivity and environmental performance. An information technology framework for construction was also developed. As the world entered the information age, the implications for the industry were also studied. Finally, the concepts of leadership, ethics and transparency and their importance on construction projects and in the construction industry were also studied. The focus here is on industry development and its application to the delivery of housing. It is suggested that effective methods should be found to reduce the tendency to duplicate studies and to effectively build on relevant findings over time. A research agenda is proposed.